Triage Decision-Making Competencies among Nurses in Disaster Response: A Study from Hospitals Disaster Affected Areas - Husna, Cut; Syakirah, Hilma; Ahyana, Ahyana (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
Aims: This study aimed to compare triage decision-making skills among nurses at general hospitals (GH) and maternal and child hospitals (MCH) in Banda Aceh, Indonesia.  Methods: This comparative study used a cross-sectional design. A total sampling technique was used involving all nurses in General Hospital (GH) and Maternal and Child Hospital, comprising 169 nurses with the totally sample in GH and MCH hospitals were 104 and 65 respondents respectively. The sample inclusion criteria were as follows: last education minimum diploma, at least six months of work experience, and working in emergency departments and intensive care. The exclusion criteria were nurses who left or study assignments during the study period.  The questionnaire used was the Triage Decision-Making Inventory (TDMI), which consists of three sub-items: cognitive ability, experience, and intuition, totaling 27 items measured on a six-point Likert scale.  Results: Data were analyzed using the Mann-Whitney U-test. The results revealed a significant difference in triage decision-making competencies among nurses in disaster response between GH and MCH hospitals, with the mean and SD (136.98±12.47, 122.66±12.43, p=0.001), respectively. For each variable of the study, there was no significant difference in the cognitive abilities (p=0.180) and experience of nurses (p=0.562) between nurses in GH and MCH hospitals. However, there was a significant difference in nurses’ intuitions (p=0.001). Conclusion: The differences in triage decision-making skills between nurses in GH and MCH hospitals are related to their perceptions of intuition, clinical experience, and cognitive ability in caring for emergency cases in both hospitals. The cognitive abilities and clinical experience of nurses in caring for patients, particularly in emergency/health crisis/disasters, may help them in triage decision-making. Therefore, it is important for hospitals to have an effective triage information system and nurses with adequate knowledge and skills in triage.